Smoking prevalance and associated risk factors among nurses in manisa - Nehir, Sevgi; Demet, Mehmet Murat; Dinç, Gönül (Journal of Dependence, 2007)
Objective: In this reaserch we aimed to determine the proportion of smoking and associated risk factors among nurses in Manisa. Method: The study grup is 615 nurses who work in hospitals and primary care units in Manisa City Center. 433 (70.0 %) of the study population accepted to join the study. Demografik informaiton form and Fagerstrom Nikotin Dependence Tests were applied to the participants. The analys of the data was made using SPSS 10,0. The data was analysed using SPSS 10.0 for Windows®. In the statistics analyses estimated rölatif risk and 95% Crude odds ratios (ORs) were calculated. Results: We determined that from 433 nurses joined to our study 42.3% (n=183) of the nurses are current smoker and 12,7% (n=55) of them were ex-smokers. Looking at the smoking behaviours, it was determined that 20.8% (n=90) nurses smoke 10 or less cigarettes, 17.6% (n=76) of them smoke 11-20 cigarettes and 4% (n=17) of them smoke 21 or more cigarettes in a day. Being widow and divorced, being in group of 40-44 years, less educational level for nursing, mental disorder history, parents’ smoking history, alcohol use were determined as risk factors for cigarette use. Conclusion: It was concluded that smoking behavior is common among nurses. It can be recommended that parents should be a proper model for their children especially in their early childhood because a proper model is more effective than a reasonable warning.Counseling and supporting activities for the people like widow or divorced people, the people who have a mental disorder is also helpful for smoking prevention.